Effect of the Board of Commissioners' Advising Role on Corporate Performance: Family Governance as a Moderating Variable - Makaryanawati Makaryanawati (Journal of International Conference Proceedings (JICP), 2019)
Improved performance is one of the company's strategic goals. Many factors can influence a corporate's performance, among others, is the advising role of the board of commissioners. This study aims to examine the influence of the advising role on corporate performance, which is moderated by family governance. The population are manufacturing companies that are listed on the IDX from 2008-2014. The sample selection uses purposive sampling and generate 792 observations. The findings that are generated are advising roles that have a positive effect on corporate performance. However, family governance weakens the influence of advising roles on corporate performance. The dominance of the family makes the board of commissioners unable to provide professional advice, thereby reducing the corporate's performance.